THE CULTURAL IDENTITY OF THE PETECAPRACTICED ON THE COPACABANA BEACH (Fiep Bulletin - online, 2015)
To unveil how the cultural identities are characterized  at the petecagame on the beach, the present article will demonstrate how such a game is practiced on Copacabana beach, Rio de Janeiro  Brazil. Taking as an example the sporting culture on that  beach, there is an intention to describe the phenomenon of the peteca on the beach. To identify the differences and similarities  of the practicing of peteca along the time on the Copacabana beach shore, in Rio de Janeiro, to identify how these spaces are created to this game and the symbolic elements presented on the  petequeiros (practititoners of peteca) imagination on the beach. The studies have an exploratory description, with a qualitative approach, based on  an interpretative ethnographic , presenting as the investigation area the  posto two - (place number 2 on the beach),  three and six of Copacabana beach. Up to this moment we may assume that the peteca is a  dynamic game and of a excellent motor simplicity; its material  has a low price. It brings in itself the tradition and a playful cultural manifestation and its manifestation on the beach space is presented in different ways and as a characteristic  leisure activity . However, the low  adherence to this game is  observed in Rio de Janeiro. Nevertheless, it is verified  a group that  developed and resists, with its own characteristics,on the beaches, creating the beach´s peteca identity. At last, these facts provoke the interest of having a higher comprehension of this sporting phenomenon and tries to focus  on the beach as an space of great human dimension . We believe that with this study we can contribute with favorable conditions to the public politics that are responsible  for the sporting activities on the beaches, looking for a better  quality of life.
Keywords: sports on the beach; sport and leisure; cultural identity; peteca game (shuttlecock).